The Effectiveness of Phonics Approach in Teaching Reading - Atika Salman Faris (IJECA (International Journal of Education and Curriculum Application), 2018)
This research aimed to determine the effectiveness of phonics approach in teaching reading for the seventh graders of SMP Negeri 1 Aikmel, East Lombok, and to what extent it is effective. This research was designed as  pre-experimental with read aloud test as the instrument to collect data. The sample of this research consisted of 36 students of SMP Negeri 1 Aikmel. The sample was taken through purposive sampling. In collecting the data, a pre-test and a post-test were given to the students. SPSS 17 for Windows and paired-sample t-test were applied to analyze the collected data. After, calculating the data, it could be known that there was a significant difference in the mean scores between pre-test and post-test, t(df=35) = 23.314 at p = 0.001, meaning that the null hypothesis was rejected and the alternative hypothesis was accepted. In a nutshell, phonics approach was significantly effective in teaching reading for the seventh graders of SMP Negeri 1 Aikmel.